Gender profile of principal investigators in a large academic clinical trials group - Luong, Vi Thi Thao; Ho, Cindy; Aedo-Lopez, Veronica; Segelov, Eva (Frontiers in Surgery, 2022)
Introduction: Gender equity in medicine has become a significant topic of discussion due to consistently low female representation in academia and leadership roles. Gender imbalance directly affects patient care. This study examined the gender and craft group of the Principal Investigators (PI) of clinical trials run by the Australasian Gastro-Intestinal Trials Group (AGITG) Methods: Publicly available data was obtained from the AGITG website. Trials were divided into upper, lower gastrointestinal cancer, miscellaneous (neuroendocrine and gastrointestinal stromal tumours). Where multiple PIs were listed, all were counted. Craft group was assigned as surgical, medical, radiation oncology or other. Results: There were 69 trials with 89 PI, where 52 trials were represented exclusively by male PIs. Of all PIs, 18 were women (20.2%); all were medical oncologists. Prior to 2005, all PIs were male. The craft group distribution of PIs was: 79% medical oncologists, 12% surgical oncologists, 8% radiation oncologist, 1% nuclear medicine physicians. Regarding trials with multiple PI’s, there were 19 in total. Of these, 11 had only male PIs, which included 5 surgeons. Females were more likely to be a co-PI (42%) as opposed to sole PI (18%). There was no gender policy publicly available on AGITG website. Conclusions: There is a low percentage of female PIs in academic oncology trials in the portfolio of this large international trials group. No trial was led by a female surgical or radiation oncologist. There is a need to understand the reasons driving the disparity so that specific strategies can be put in place.